2011
DOI: 10.1039/c0sm01455a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles-induced anisotropic shrinkage of polymer emulsion droplets

Abstract: We here report magnetic nanoparticles (NPs)-induced buckling instability and anisotropic shrinkage behavior of polymer emulsion droplets. The oil-in-water emulsion is stabilized by the surfactant, and NPs are dispersed into the oil phase. The surface ligands (oleic acid and oleylamine) number of the NPs is an important factor to affect the shrinkage process. When a part of the ligands of the NPs is removed, the NPs show good interface attachment at the oilwater interface even with the presence of a large amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The inner particle surface was rougher than the outer, with the appearance of cracks. It has been reported that the magnetic NPs at the interface could induce the buckling instability of emulsion droplets during the solvent removal, causing the shrinkage of particles . This is consistent with our proposed W/O/W emulsion formation, namely, hydrophilic IONPs have been captured into the inner water phase (Figure ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The inner particle surface was rougher than the outer, with the appearance of cracks. It has been reported that the magnetic NPs at the interface could induce the buckling instability of emulsion droplets during the solvent removal, causing the shrinkage of particles . This is consistent with our proposed W/O/W emulsion formation, namely, hydrophilic IONPs have been captured into the inner water phase (Figure ).…”
Section: Resultssupporting
confidence: 91%
“…This led to the formation of the closed‐hollow microparticles after drying [Figure (c)]. IONPs‐induced anisotropic shrinkage caused cracks on the surface or collapse of polymer particles as shown in a higher magnification [Figure (b)]. To encapsulate hydrophobic IONPs into PLA nanoparticles, the one‐step W/O/W emulsion was not necessary and RT was enough to capture hydrophobic IONPs [Figure (b), RT], corresponding to sample F in Table [Figure (d)].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, thermogravimetric analysis (TGA) is a widely used technique to evaluate the organic content on the surface of NPs [62,63,64,65,66]. The density of polystyrene on the nanoparticle surface was calculated according to TGA.…”
Section: Resultsmentioning
confidence: 99%
“…With the loss of the toluene, the surface area of the capsule decreases. The onset of collapse takes place when the critical pressure inside the spherical shell cannot resist the external pressure . As seen in Figure , three capsules were imaged to record the collapse of their shells in the shrinking process.…”
Section: Methodsmentioning
confidence: 99%